PENDAMPINGAN DESAIN SHOW ROOM SEBAGAI MEDIA PEMASARAN HASIL KARYA WARGA BINAAN DI LEMBAGA PERMASYARAKATAN KELAS 1 MALANG - Fauzan, Slamet; Pramono, Andy; Putri, Dhika Maha; Al Ansyorie, M. Musthofa; Indriyani, Lifiya (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, 2021)
Class I Malang Correctional Institution is one of the institutions that becomes a means of training for people who have committed crimes or prisoners to return to being a society that has behavior in accordance with both religious and social norms. Penitentiaries carry out 2 types, namely personality development and independence development. The implementation of LAPAS Class 1 independence guidance Malang carries out skills training for all assisted residents so that when the assisted residents leave the LAPAS premises they have skills that can be used to support their lives in the midst of the community. Penitentiaries The role of self-reliance development provides skills by providing guidance in the form of providing material on skills, providing the necessary infrastructure, and directly assisting inmates so that the inmates are able to make crafts well. IN LAPAS Class 1 Malang, the types of skills provided are from wood art, painting, textile art to carving. The branch of art produces products that have high aesthetic value. However, the work of the assisted residents has not been able to be exposed to the wider community so that the holding of this show room assistance can be used as a forum to introduce the results of art skills to the community in order to get appreciation and generate people's purchasing power as well as to provide opportunities for the assisted residents so that their art works have a market in the midst of society so that when the assisted residents return to the community they are able to become a productive society to support their economy. The community service method is carried out by the development method with basic modifications which results in showroom design products that are the skillful works of the community members